Antioxidant and Hepatoprotective Activity of Ascorbic Acid Against Diclofenac Induced Hepatotoxicity in Rats - Bose, Sandeep; Darbar, Soumendra; Chatterjee, Nilendra; Roy, Bikash; Kumar Chattaraj, Tapas; Kumar Pal, Tapan (Asian Journal of Chemistry, 2010)
In this study, the effect of diclofenac sodium induced liver damage in rats was investigated, morphologically and biochemically. Damaging effects of reactive oxygen species (ROS) on living systems are well documented. They include oxidative attack on vital cell constituents. Administration of diclofenac sodium (150 mg/kg/d) for 28 d produced severe liver injury, as demonstrated by dramatic elevation of serum hepatospecific markers like serum glutamate pyruvate transaminase (SGPT), serum glutamate oxaloacetate transanimase (SGOT), serum alkaline phosphatase (ALP), serum acid phosphatase (SAP), blood urea nitrogen (BUN), serum total cholesterol and bilirubin levels and typical histopathological changes, hepatocyte necrosis or apoptosis, haemorrhage, fatty degeneration, etc. In addition, diclofenac sodium administration caused oxidative stress in rats, as evidenced by increased ROS production and malondialdehyde (MDA) concentrations in the liver of rats, along with a remarkable reduction in hepatic superoxide dismutase (SOD), catalase (CAT) activity and reduced glutathione (GSH) content. However, simultaneous treatment with ascorbic acid as a food supplement (200 mg/kg/d) significantly attenuated diclofenac sodium induced hepatotoxicity. The results showed that serum SGOT, SGPT, ALP, SAP, BUN, cholesterol, bilirubin levels and hepatic MDA content as well as ROS production were reduced dramatically and hepatic SOD, CAT activity and GSH content were restored remarkably by ascorbic acid supplementation, as compared to the diclofenac sodium treated rats. Moreover, the histopathological damage of liver and the number of apoptotic hepatocytes were also significantly ameliorated by ascorbic acid treatment. It is, therefore suggested that ascorbic acid can provide a definite protective effect against acute hepatic injury caused by diclofenac sodium in rats, which may mainly be associated with its antioxidative effect.